The RCCDE learning in understanding the concept of seawater invertebrates in tabuhan island bangsring banyuwangi, indonesia - Siti Roudlotul Hikamah; Hariyanto Hariyanto (JPBIO (Jurnal Pendidikan Biologi), 2022)
This research is essential to empower the understanding of the concept of invertebrate material that is difficult to observe because its habitat is in seawater. This research aims to reveal the effectiveness of the Reading Concept Map Connection Discussion Evaluation (RCCDE) learning model on students' conceptual understanding of Seawater Invertebrates. This type of research is a quasi-experimental, one-group pre-test and post-test design. The research data were analyzed using the N-gain score. The analysis results showed that the class average N-gain score was 0.71, which was greater than the N-gain score of 0.7 (g > 0.7). This means that the RCCDE model is effective for students in understanding the concept of seawater invertebrates because it has high criteria. The individual average normalized gain analysis results found 20 students with a high standard of g > 0.7 and 14 students with a gain score of 0.3 > g 0.7. On the medium criterion, there were no students with a score of g 0.3. This shows the effectiveness of the RCCDE syntax in empowering concept understanding. Students play an active role in learning activities to find their problems and look for answers until they find answers and solutions.